Estimate of the Arctic Convective Boundary Layer Height from Lidar Observations: A Case Study. (9th April 2012) - Di Liberto, L.; Angelini, F.; Pietroni, I.; Cairo, F.; Di Donfrancesco, G.; Viola, A.; Argentini, S.; Fierli, F.; Gobbi, G.; Maturilli, M.; Neuber, R.; Snels, M.
Abstract : A new automated small size lidar system (microlidar or MULID) has been developed and employed to perform aerosol measurements since March 2010 at Ny Ålesund (78.9 ° N, 11.9 ° E ), Svalbard. The lidar observations have been used to estimate the PBL height by using the gradient method based on abrupt changes in the vertical aerosol profile and monitor its temporal evolution. The scope of the present study is to compare several approaches to estimate the PBL height, by using lidar observations, meteorological measurements by radio soundings, and a zero-order one-dimensional model based on a parameterization of the turbulent kinetic energy budget within the mixing layer, under the assumptions of horizontal homogeneity, and neglecting radiation and latent heat effects. A case study is presented here for a convective PBL, observed in June 2010 in order to verify whether the Gradient Method can be applied to lidar measurements in the Arctic region to obtain the PBL height. The results obtained are in good agreement with the PBL height estimated by the analysis of thermodynamic measurements obtained from radio sounding and with the model.